2018
DOI: 10.1111/cei.13212
|View full text |Cite
|
Sign up to set email alerts
|

Dietary soyasaponin attenuates 2,4-dinitrofluorobenzene-induced contact hypersensitivity via gut microbiota in mice

Abstract: Soyasaponins (SSs) are abundant in soybeans and display inhibitory activity against contact hypersensitivity (CHS), which is often used as a mouse model for allergic contact dermatitis (ACD); however, their therapeutic mechanisms remain unknown. Here, we attempted to clarify the role of gut microbiota in the inhibition of CHS by dietary soyasaponins. For antibiotic treatment, mice were administered a mixture of ciprofloxacin and metronidazole or vancomycin. These antibiotics and SSs were given to mice via drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Bacteria were recovered from the lysates of fecal samples using a FastDNA Spin Kit for Soil (MP Biomedicals). Polymerase chain reaction and sequencing were performed using the Illumina MiSeq platform (Illumina, San Diego), as described previously (Nagano et al., 2019c). Taxonomic analysis of the 16S rDNA sequences was conducted by the TechnoSuruga Laboratory (Shizuoka, Japan) based on the Ribosomal Database Project using Metagenome@Kin analysis software (World Fusion, Tokyo).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria were recovered from the lysates of fecal samples using a FastDNA Spin Kit for Soil (MP Biomedicals). Polymerase chain reaction and sequencing were performed using the Illumina MiSeq platform (Illumina, San Diego), as described previously (Nagano et al., 2019c). Taxonomic analysis of the 16S rDNA sequences was conducted by the TechnoSuruga Laboratory (Shizuoka, Japan) based on the Ribosomal Database Project using Metagenome@Kin analysis software (World Fusion, Tokyo).…”
Section: Methodsmentioning
confidence: 99%
“…This antibiotic treatment reduced the number of regulatory T (T reg ) cells in auricular lymph nodes and spleen, and completely altered the gut microbiota composition in the SS‐treated mice. These results indicated that the observed reduction in CHS‐inhibitory activity was likely due to an altered gut microbiota composition that resulted in a reduction in T reg cells (Nagano et al., 2019c). However, the CHS‐inhibitory effects of diets containing a mixture of SIs and SSs and the role of the intestinal microbiota are unknown.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, there were no negative effects on its performance, intestinal morphology and organ index with SS supplementation to the diet of mice [26]. SS alleviated 2,4-dinitro uoro benzene (DNFB)-induced intestinal micro ora imbalance in mice [31]. Most of these studies were concentrated in the medical eld.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the proliferation of Staphylococcus aureus and Escherichia coli were inhibited by SS [9; 16]. SS could also alleviate allergic skin reactions in mice via improving the intestinal micro ora [31]. Besides, some scholars tried to ferment soybean meal with Lactobacillus pentosus, and nally detected the production of soyasaponol and genistein.…”
Section: Introductionmentioning
confidence: 99%